The Scholarship Girl: Life Writing - George, Abigail (Book collections on Project MUSE., 2019)
Pushcart Prize nominated Abigail George is a South African blogger at Goodreads, essayist, poet, playwright, short story writer and novelist. She briefly studied film at the Newtown Film and Television School in Johannesburg. Her writing has appeared in many anthologies in South Africa and online in e-zines across Africa, Asia, Europe, and the United States. She is the recipient of writing grants from the National Arts Council in Johannesburg, the Centre for the Book in Cape Town and ECPACC (Eastern Cape Provincial Arts and Culture Council) in East London.